The Role of Celebrity Endorser, Product Attractiveness in Improving Brand Image - Mardiyono, Aris; Soesanto, Harry (Universitas Proklamasi 45, 2023)
The purpose of this study is to develop the concept of celebrity endorsers, and product attractiveness to purchasing decisions with brand image as an intervening variable. A sample of 137 respondents consisted of fashion blazer owners in the city of Semarang. Retrieval of data by purposive random sampling method. The analysis tool uses Structural Equation Modeling with the application of the Moment of Structural Analysis program version 21. The findings of this study, the influence of celebrity endorsers, product attractiveness, and brand perception in a favorable and significant way. Celebrity endorsers, product attractiveness, and brand perception affect purchasing decisions in a positive and significant way.